Epidemiology of Epstein-Barr virus infection and infectious mononucleosis in the United Kingdom - Ashvin Kuri; Benjamin Meir Jacobs; Nikki Vickaryous; Julia Pakpoor; Jaap Middeldorp; Gavin Giovannoni; Ruth Dobson (BMC, 2020)
Abstract Background Epstein-Barr Virus (EBV) is a ubiquitous gamma-herpesvirus with which ~ 95% of the healthy population is infected. EBV infection has been implicated in a range of haematological malignancies and autoimmune diseases. Delayed primary EBV infection increases the risk of subsequent complications. Contemporaneous seroepidemiological data is needed to establish best approaches for successful vaccination strategies in the future. Methods We conducted a sero-epidemiological survey using serum samples from 2325 individuals between 0 and 25 years old to assess prevalence of detectable anti-EBV antibodies. Second, we conducted a retrospective review of Hospital Episode Statistics to examine changes in Infectious Mononucleosis (IM) incidence over time. We then conducted a large case-control study of 6306 prevalent IM cases and 1,009,971 unmatched controls extracted from an East London GP database to determine exposures associated with IM. Results 1982/2325 individuals (85.3%) were EBV seropositive. EBV seropositivity increased more rapidly in females than males during adolescence (age 10-15). Between 2002 and 2013, the incidence of IM (derived from hospital admissions data) increased. Exposures associated with an increased risk of IM were lower BMI, White ethnicity, and not smoking. Conclusions We report that overall EBV seroprevalence in the UK appears to have increased, and that a sharp increase in EBV seropositivity is seen in adolescent females, but not males. The incidence of IM requiring hospitalisation is increasing. Exposures associated with prevalent IM in a diverse population include white ethnicity, lower BMI, and never-smoking, and these exposures interact with each other. Lastly, we provide pilot evidence suggesting that antibody responses to vaccine and commonly encountered pathogens do not appear to be diminished among EBV-seronegative individuals. Our findings could help to inform vaccine study designs in efforts to prevent IM and late complications of EBV infection, such as Multiple Sclerosis.